1989
DOI: 10.1113/jphysiol.1989.sp017677
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of secretagogue‐induced amylase secretion in pancreatic acini of cold‐exposed rats.

Abstract: SUMMARY1. The influence of prolonged exposure to a low ambient temperature on the pancreatic exocrine function was investigated in rats. Amylase concentration in acini prepared from rats housed at 5 TC for 2 weeks was specifically and dramatically reduced. The enzyme activity relative to acinar DNA concentration was only 48 % of that of control acini obtained from rats reared at the thermoneutral temperature of 25 'C. Amylase content relative to acinar protein concentration also decreased by 35 %. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…2 In the salivary gland, Ruellan et al 3 reported that CCK octapeptide (CCK‐8) caused lipase secretion from the rat Ebner gland. On the other hand, Habara 4 has shown that there is no comparable change in rat parotid gland amylase to the treatment of CCK‐8. Recently, Purushotham et al 5 also showed that CCK‐8 alone does not influence the activities of amylase, protein kinase C, and 3‐kinase phosphatidylinositol 3‐kinase in the parotid gland.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the salivary gland, Ruellan et al 3 reported that CCK octapeptide (CCK‐8) caused lipase secretion from the rat Ebner gland. On the other hand, Habara 4 has shown that there is no comparable change in rat parotid gland amylase to the treatment of CCK‐8. Recently, Purushotham et al 5 also showed that CCK‐8 alone does not influence the activities of amylase, protein kinase C, and 3‐kinase phosphatidylinositol 3‐kinase in the parotid gland.…”
Section: Introductionmentioning
confidence: 99%